Clinical bleeding and thrombin generation in admissions to critical care with prolonged prothrombin time: an exploratory study. Issue 6 (10th April 2018) - Stanworth, Simon J.; Desborough, Michael J.R.; Simons, Gemma; Seeney, Frances; Powter, Gillian; MacDonald, Stephen; McKechnie, Stuart; Green, Laura; Young, Neil; Walsh, Timothy; Laffan, Mike A.
Abstract : BACKGROUND: Prolongation of prothrombin time (PT) is often recorded in critical illness, but has limited ability to predict risk of bleeding. This exploratory study was aimed at assessing a role for thrombin generation (TG) to predict bleeding. STUDY DESIGN AND METHODS: TG was measured by calibrated automated thrombography in admissions to intensive care with prolonged PT. Bleeding events were recorded up to Day 5 after enrollment and correlated with results of PT ratio (PTR) and variables of TG. RESULTS: A total of 306 patients were recruited. A total of 101 bleeding events developed in 46 patients during the period of observation. Many patients with prolonged PT had endogenous thrombin potential (ETP), which was within the normal range (120/251 patients, 47.8%) or even elevated (8%). Although some patients had a reduction in ETP or peak thrombin, these were present over a wide range of PTR. There was no suggestion by receiver operating characteristic analysis that variables of conventional TG were sensitive at predicting bleeding. No bleeding events were documented in patients defined as ETP high, despite elevated PTR. CONCLUSION: Future studies need to explore a role for alternatives tests of coagulation in critical illness. Development of TG assays is required to positively identify more patients at increased bleeding risk or to exclude a larger number at low risk and how this relates to subgroups, such as patients with liver disease, and the need for prophylactic plasma transfusion.